1997
DOI: 10.1046/j.1365-2605.1997.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic sperm injection using surgically retrieved epididymal and testicular spermatozoa in cases of obstructive and non‐obstructive azoospermia

Abstract: This was a retrospective study of 115 patients who underwent 124 cycles of ICSI using surgically retrieved spermatozoa. The objective was to compare the results of ICSI in patients with obstructive azoospermia using epididymal spermatozoa (36 cycles) or testicular spermatozoa (58 cycles) with ICSI in patients with non-obstructive azoospermia using testicular spermatozoa (30 cycles). When epididymal spermatozoa were used for ICSI, the fertilization rate per injected metaphase-II oocyte and the clinical pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 6 publications
3
14
0
2
Order By: Relevance
“…There was also no difference in pregnancy outcome between two groups, which is in consensus with many studies. 22,23 However, some studies have found lower outcome of ICSI with surgically retrieved sperm vis ejaculated sperms. 24 In our patients, results of ICSI cycles using epididymal and testicular sperm had similar outcomes showing that source of sperm or etiology does not affect sperm injection outcome as also shown in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…There was also no difference in pregnancy outcome between two groups, which is in consensus with many studies. 22,23 However, some studies have found lower outcome of ICSI with surgically retrieved sperm vis ejaculated sperms. 24 In our patients, results of ICSI cycles using epididymal and testicular sperm had similar outcomes showing that source of sperm or etiology does not affect sperm injection outcome as also shown in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported in 1993 that the use of testicular spermatozoa in ICSI for cases of obstructive azoospermia could achieve fertilization and pregnancy (Craft et al, 1993;Schoysman et al, 1993a,b). Following that, other different programmes reported the use of testicular spermatozoa with ICSI Bourne et al, 1995b;Nagy et al, 1995b;Silber et al, 1995a;Fahmy et al, 1996;Mansour et al, 1996a). Recently, the indications for testicular sperm extraction (TESE) and ICSI have been expanded to include cases with non-obstructive azoospermia due to severe impairment of spermatogenesis (Devroey et al, 1995;Tournaye et al, 1995;Gil-Salom et al, 1995;Kahraman et al, 1996b;Silber et al, 1996;Mansour et al 1997a;Tournaye et al, 1997).…”
Section: Clinical Application Of Icsimentioning
confidence: 99%
“…Therefore, clinicians and scientists providing ICSI for infertile men must be aware of the genetic implications of male factor infertility. ICSI using surgically retrieved spermatozoa has achieved good fertilization and pregnancy rates that are comparable to those for ICSI with ejaculated spermatozoa (Craft et al, 1993;FIVNAT, 1993;Silber et al, 1994;Tournaye et al, 1994;Hovatta et al, 1995;Fahmy et al, 1996;Tarlatzis, 1996;Mansour et al, 1997a). Different researchers have studied fertilization and pregnancy rates after ICSI using epididymal versus testicular spermatozoa (Hovatta et al, 1995;Nagy et al, 1995b;Silber et al, 1995a;Mansour et al, 1997a;Tarlatzis, 1996).…”
Section: Potential Risks Of Icsimentioning
confidence: 99%
“…Отрицательный результат, по мнению авторов [5], был связан как с изначально маленьким объемом яичек, так и со зре-лым возрастом пациентов. ФСГ, благодаря его дей-ствию на клетки Сертоли и гематотестикулятный барьер, играет важную роль в регуляции микрова-скулярности яичек.…”
unclassified